PENERAPAN BUDAYA SUFISTIK TERHADAP MORAL ELEVATION PARA SANTRI DI PESANTREN PUTRA TEBUIRENG JOMBANG JAWA TIMUR - Wening Purbatin Palupi Soenjoto; Husna Ni’matul Ulya (IAIN Ponorogo, 2021)
This research was conducted to analyze and describe the application of Sufistic culture to moral elevation in the formation of moral elevation of students at the Putra Tebuireng Islamic Boarding School in Jombang, East Java. The location of the study was carried out by the Islamic boarding school male Tebuireng Jombang. The research method used is a qualitative method using descriptive analysis and triangulation techniques. The research respondents consisted of 30 people aged 16-24 years. The results showed that the application of Sufistic culture to the moral elevation of male students and the formation of moral elevation in the world of pesantren education needed a consistent process and support from all parties. namely the creed, sharia, and morals as a support for the occurrence of moral elevation.